1981
DOI: 10.1203/00006450-198104001-01483
|View full text |Cite
|
Sign up to set email alerts
|

1454 a Pathologic Reappraisal of Kernicterus

Abstract: Continuous monitoring of v i t a l s i g n s , e . g . temperature, blood pressure, heart and r e s p i r a t i o n r a t e s , and E C G , f o r the care of c r i t i c a l l y s i c k infants has become an established hospital routine. W e have compared various non-invasive and invasive continuous Pa02 monitors with a r t e r i a l blood Pa02 levels and find t h a t there i s a considerable c o r r e l a t i o n between the values obtained by d i f f e r e n t procedures. Continuous monitoring procedures per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…This experimental model supports the proposal that yellow staining cannot be equated with bilirubin toxicity and provides a possible explanation for the neuropathological observations of Turkel et al (26). In many sick premature infants with yellow staining, they found spongy changes in brain consistent with interstitial edema (or interstitial bilirubin-albumin), but few changes in neurons that could be attributed to bilirubin.…”
Section: Discussionsupporting
confidence: 73%
“…This experimental model supports the proposal that yellow staining cannot be equated with bilirubin toxicity and provides a possible explanation for the neuropathological observations of Turkel et al (26). In many sick premature infants with yellow staining, they found spongy changes in brain consistent with interstitial edema (or interstitial bilirubin-albumin), but few changes in neurons that could be attributed to bilirubin.…”
Section: Discussionsupporting
confidence: 73%
“…But, in reviewing this data, Wennberg and Ahlfors (46) found that the combination of unbound bilirubin levels and serum pH resulted in a much better correlation with risk for kernicterus. Furthermore, Levine et al (26) presented evidence which implicates opening of the bloodbrain barrier in the pathogenesis of gross staining of the brain by bilirubin, and Turkel et al (43) pointed out that gross bilirubin staining of the neonatal brain is often not associated with histopathologic changes indicative of bilirubin toxicity. These studies indicate the need for further studies to carefully delineate the relationships between serum unbound bilirubin levels, brain bilirubin levels, physiologic and pathologic signs of bilirubininduced neurocytotoxicity, and grossly visible staining of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem cohort studies introduced controversy about the role of acidosis. 3,11 Some did correlate free serum unconjugated bilirubin with autopsy-confirmed preterm kernicterus. 36 Focusing on sensorineural deafness without cerebral palsy in preterms of gestational age Ͻ34 weeks and TSB peak level Ͼ240 mol/L (14 mg/dL), de Vries et al in 1985 37 correlated bilirubin toxicity with spells of respiratory acidosis and with duration of hyperbilirubinemia (5 of 12 deaf children with at least 48 hours of TSB Ͼ240 mol/L, versus 1 of 12 matched control subjects).…”
Section: Discussionmentioning
confidence: 99%
“…11 Macroscopic staining of brain areas occurs in the absence of neuronal cell loss, troubling the histopathologic diagnosis. Regional exudation of bilirubin should not be equated with kernicterus.…”
Section: Discussionmentioning
confidence: 99%